The presence of eccentric hyperpigmentation should raise the suspicion of melanoma. (5th June 2020) - Borsari, S.; Peccerillo, F.; Pampena, R.; Lai, M.; Spadafora, M.; Moscarella, E.; Lallas, A.; Pizzichetta, M.A.; Zalaudek, I.; Del Regno, L.; Peris, K.; Pellacani, G; et al.
Abstract: Background: Melanocytic lesions with eccentric hyperpigmentation (EH), even though without other dermatoscopic features of melanoma, are often excised. Objective: Aiming to understand whether the EH in a pigmented lesion is an accurate criterion of malignancy, we evaluated the capability of two evaluators, with different expertise, to correctly diagnose a melanoma when analysing a given lesion in toto versus a partial analysis, with only the EH or the non‐hyperpigmented portion (non‐EH) visible. Methods: Dermatoscopic images of 240 lesions (107 melanomas and 133 nevi) typified by EH were selected. Facial, acral, mucosal lesions and lesions showing clear‐cut features of melanoma (except for atypical network) were excluded. Clinical and dermoscopic features (main pattern and numbers of colours) were described for all cases. Each image was split in two through a software so that only the EH or the non‐EH was visible. Two blinded evaluators examined three sets of images, two with customized images and one with the non‐modified ones: they were asked to give a dichotomous diagnosis (melanoma or nevus) for each image. Results: Melanomas were significantly more frequently typified by colour variegation (3 colours in 44.8% and 4 colours in 41.1% of cases) and atypical network (88.1% in the EH). No significant differences in diagnostic accuracy emerged between the two evaluators. Sensitivity improved in the evaluation of the whole lesions (mean sensitivity 89.7%) in comparison with the evaluation of EH or non‐EH alone (72.7–62.6%). Specificity increased when evaluating the EH (54.1%). Positive predictive value (PPV) and likelihood ratio (LR+) of EH resulted 52.3% and 1.4, meaning that in one case out of two with EH is a melanoma. Conclusions: Lesions with EH are challenging, regardless of dermoscopic experience. The EH is a robust criterion for malignancy, since the evaluation of the whole lesion, through an intralesional comparative approach, increases sensitivity.